Fighting Ships of World War II - Westwood, J. N. (London Book Club Associates, 1977)
Battleships, aircraft carriers, cruisers, destroyers, submarines, and escorts.
Includes Index and Illustrations.
Edition from jacket.
Keywords: Warships -- Submarines (Ships) -- Military Campaigns